Dystrophin-deficient dogs with reduced myostatin have unequal muscle growth and greater joint contractures. Issue 1 (December 2016) - Kornegay, Joe; Bogan, Daniel; Bogan, Janet; Dow, Jennifer; Wang, Jiahui; Fan, Zheng; Liu, Naili; Warsing, Leigh; Grange, Robert; Ahn, Mihye; Balog-Alvarez, Cynthia; Cotten, Steven; et al.
Abstract Background Myostatin (Mstn ) is a negative regulator of muscle growth whose inhibition promotes muscle growth and regeneration. Dystrophin-deficient mdx mice in which myostatin is knocked out or inhibited postnatally have a less severe phenotype with greater total mass and strength and less fibrosis and fatty replacement of muscles than mdx mice with wild-type myostatin expression. Dogs with golden retriever muscular dystrophy (GRMD) have previously been noted to have increased muscle mass and reduced fibrosis after systemic postnatal myostatin inhibition. Based partly on these results, myostatin inhibitors are in development for use in human muscular dystrophies. However, persisting concerns regarding the effects of long-term and profound myostatin inhibition will not be easily or imminently answered in clinical trials. Methods To address these concerns, we developed a canine (GRippet ) model by crossbreeding dystrophin-deficient GRMD dogs withMstn -heterozygous (Mstn +/− ) whippets. A total of fourGRippets (dystrophic andMstn +/− ), three GRMD (dystrophic andMstn wild-type) dogs, and three non-dystrophic controls from two litters were evaluated. Results Myostatin messenger ribonucleic acid (mRNA) and protein levels were downregulated in both GRMD andGRippet dogs.GRippets had more severe postural changes and larger (more restricted) maximal joint flexion angles, apparently due to further exaggeration of disproportionate effects on muscle size. Flexors such as the cranial sartorius were more hypertrophied on magnetic resonance imaging (MRI) in theGRippets, while extensors, including the quadriceps femoris, underwent greater atrophy. Myostatin protein levels negatively correlated with relative cranial sartorius muscle cross-sectional area on MRI, supporting a role in disproportionate muscle size. Activin receptor type IIB (ActRIIB) expression was higher in dystrophic versus control dogs, consistent with physiologic feedback between myostatin and ActRIIB. However, there was no differential expression between GRMD andGRippet dogs. Satellite cell exhaustion was not observed inGRippets up to 3 years of age. Conclusions Partial myostatin loss may exaggerate selective muscle hypertrophy or atrophy/hypoplasia in GRMD dogs and worsen contractures. While muscle imbalance is not a feature of myostatin inhibition in mdx mice, findings in a larger animal model could translate to human experience with myostatin inhibitors.